50.7k views
3 votes
or simplicity, let X=M G = 1 I = 2 if you like decimals C = 3 + 0.75Y or if you prefer fractions C = 3 + 3/4Y the simple multiplier is equal to

User Textral
by
4.8k points

1 Answer

7 votes

Answer:

the simple multiplier is equal to 4

Explanation:

Given that:

Y= C + I + G + (X - M)

the average expenditure Y must be equal to the totality of the output

If C = 3 + 0.75Y

here;

the marginal propensity consumed MPC = 0.75

Then,

Y = 3 + 0.75Y + 2 + 1

Y = 6+0.75 Y

Y - 0.75 Y = 6

0.25 Y = 6

Y = 6/0.25

Y = 24

However, the simple multiplier can be expressed as:


= (1)/(1-MPC)


= (1)/(1-0.75)

=
(1)/(0.25)

= 4

User Alish Giri
by
5.6k points